Insight of Al-Sayyid al-Shaheed Mohammad Baqir al-Sadr on Iqtishad - Mirakhor, Abbas; Alaabed, Alaa (University of Darussalam Gontor Press, 2024)
April 9 marked the anniversary of the martyrdom of one of the most brilliant scholars of the late 20th century, Ayatullah al-Sayyid al-Shaheed Muhammad Baqir al-Sadr, RidhwanuAllahi ta’aala ‘alayh. Al-Sayyid al-Shaheed was an extraordinary and unique genius whose personal and intellectual accomplishments as a believing and practicing Muslim serve as example for others striving for perfection intended for humans by their Creator. While the writings of al-Sadr were quite timely and important in his own time, understanding them at the present is crucial as the search for alternative socio-economic paradigms that can more effectively respond to the problems of humanity has intensified. In all of his discourses, al-Sadr was a first-rate logician who accorded logic and objective truth central and active roles without losing an opportunity to display the passion of his belief that Islam provides solutions to problems societies face. Al-Sadr’s writings constitute an integrated and interrelated whole. Singling out a specific topic in exclusion of analysis of how it is related to his philosophy does not do justice to him, to his writings or to his readers. That said, this paper is a modest attempt to provide a brief commentary on a number of al-Sadr’s brilliant insights in presenting the theory and practice of Iqtisad (Islam’s vision of ideal economy). The point bears emphasis that this paper is not a commentary on the entirety of the views of al-Sadr’s on Iqtisad; to do some degree of justice to his views requires volumes. The paper instead focuses on some of his insights—those that economic analysis itself discovered years after him, with the purpose of indicating that the Iqtisadi contributions of al-Sadr and his genius deserve far deeper and more intensive scholarly treatment than they have received so far. April 9 marked the anniversary of the martyrdom of one of the most brilliant scholars of the late 20th century, Ayatullah al-Sayyid al-Shaheed Muhammad Baqir al-Sadr, RidhwanuAllahi ta’aala ‘alayh. Al-Sayyid al-Shaheed was an extraordinary and unique genius whose personal and intellectual accomplishments as a believing and practicing Muslim were those of an archetypal human that serves as example for others striving for perfection intended for humans by their Creator. Those who knew him well have written and spoken about his personal integrity, disposition (akhlaq), compassion, commitment, modesty, courage and charisma.(Al-Sayyid al- ‘Allamah ‘Ammar Abu Ragheef, 1989)[1] Al-Sadr will continue to inspire generations as an example of a human personality fully immersed in and completely devoted to the high values and ideals of Islam. The way he lived his life, the sacrifices he made, and the immensely valuable intellectual legacy he left behind will continue to serve as a beacon of virtuous conduct, effort and sacrifice on behalf of human freedom and dignity, social justice, truth and tolerance. Aside from being a model and standard of what it means to live a life in full compliance with the high values and ideals of Islam, he was a towering intellect who set for himself a grand and difficult task of analytically rejuvenating Islamic thought in accordance with the rigor of logic and analysis demanded by his time. He did so systematically with meticulous logic presented in a way accessible to his contemporaries–especially the young Muslims alienated from Islam and seduced by “modern” ideologies. In the process, he challenged the philosophical, social, political, and economic foundations of dominant ideologies of his time. He understood well that the current compartmentalized and specialized approach to knowledge was inadequate in representing Islam’s alternative solutions to socio-political and economic problems of mankind. Accordingly, his approach to scientific revitalization and representation of the teachings of Islam—based rigorously on the Qur’an and Sunnah–was far deeper, broader, and more coherent than other contemporary efforts. He envisioned Islam’s teachings as a unified system—a network of interrelated and eminently empirical set of rules compliance with which guaranteed spiritual felicity and material prosperity for human societies. The depth and the breadth of the full spectrum of al-Sadr’s intellectual legacy fills one with a sense of awe, humility, and admiration, even four decades after his martyrdom. This impression becomes even more forceful when one realizes the early age in which al-Sayyid al-Shaheed al-Sadr began his study of western schools of thought, along with the traditional curriculum of seminaries. According to a biographer, one of his teachers in grade school with Marxist tendencies reported that at the age of twelve, al-Sadr asked him for loan of books on Marxism. Astonishing his teacher, al-Sadr provided him with answers to several questions about Marxism that had engaged his teacher’s mind for some time, while returning the books he had borrowed. Two of his major works, Falsafatuna and Iqtisaduna, were published before the age of thirty. These books display a surprising masterly grasp of the main western ideas of his time. Given the limited scholarly sources available in Arabic translation at the time, one can only wonder whether his scholarly contributions would have been much more enriched had a wider bibliography of topics of his interest published at the time in other languages were available to him. One would be justified in answering the query in the affirmative given al-Sadr’s genius